A systems approach to improving timeliness of immunisation - Bailie, R.; Si, D.; Dowden, M.; Kennedy, C.; Selvey, C.; Cox, R.; O'Donohue, L.; Liddle, H.; Connors, C.; Thompson, Sandra; Burke, H.; Brown, A. (Elsevier, 2009)
Timeliness of immunisation is important in achieving a protective effect at the individual and population levels. Recent international research has highlighted the importance of organisational features of the health system in timely immunisation. This paper reports on an analysis of the availability of records of timely delivery of childhood immunisations in Indigenous primary care services and organisational features of vaccination programs in different jurisdictions in Australia. The findings demonstrate wide variation in recorded timely delivery of immunisations between health centres within and between jurisdictions. Significant deficiencies in the approach to delivery and recording of immunisations appear to be principally related to fragmented systems of delivery, recording and communication between child health and primary care services. Understanding these deficiencies presents opportunities for improving timely immunisation.